Analysis of Beginning Reading Difficulties in Students Class II SDN 2 Mayonglor - Ana Latifatul Hikmah; Fiiki Nur Azizah; Lovika Ardana Riswari (Demagogi: Journal of Social Sciences, Economics and Education, 2024)
Beginning reading is the initial stage of learning to read which focuses on recognizing shapes and letters related to words, and provides a foundation for children to progress to the beginning stage of reading. The aim of this research is to identify difficulties in beginning reading comprehension in class II of SD Negeri 2 Mayonglor. The research method used in this research is a descriptive method with a qualitative approach. The data collection methods used in this research were observation and questionnaires. Researchers identified three students with reading comprehension difficulties. Basically, students are good at writing letters A-Z, but when these letters are written in words or sentences, they have difficulty writing some letters. Therefore, students should pay attention to the words spoken and the letters written in sentences.